Cytoprotective Role of Omentin Against Oxidative Stress-Induced Vascular Endothelial Cells Injury - Kamaruddin, Nur Aqilah Binti; Fong, Lai Yen; Tan, Jun Jie; Abdullah, Muhammad Nazrul Hakim; Cheema, Manraj Singh; Bin Yakop, Fahmi; Yong, Yoke Keong (MDPI, 2024)
Indexed by WOS/ Scopus